2013
DOI: 10.1098/rspb.2013.2242
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial farming by the fungusMorchella crassipes

Abstract: The interactions between bacteria and fungi, the main actors of the soil microbiome, remain poorly studied. Here, we show that the saprotrophic and ectomycorrhizal soil fungus Morchella crassipes acts as a bacterial farmer of Pseudomonas putida, which serves as a model soil bacterium. Farming by M. crassipes consists of bacterial dispersal, bacterial rearing with fungal exudates, as well as harvesting and translocation of bacterial carbon. The different phases were confirmed experimentally using cell counting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 54 publications
(96 reference statements)
2
75
0
1
Order By: Relevance
“…Recent work suggests that the manner in which PHB resources are hoarded is conditional, with a rhizobial strain producing fewer high-PHB cells when low competitor density predicts only short-term starvation (118) and can thus be understood as a hoarding strategy in response to competition. This system, and others like Dictyostelium farming (85) and the ectomycorrhizal soil fungus Morchella crassipes farming Pseudomonas putida bacteria as a carbon source (86), can be used to study under what conditions scarce resources are held, so they can be either used later or traded for a greater profit in the future.…”
Section: The Evolution Of Microbial Markets Frommentioning
confidence: 99%
“…Recent work suggests that the manner in which PHB resources are hoarded is conditional, with a rhizobial strain producing fewer high-PHB cells when low competitor density predicts only short-term starvation (118) and can thus be understood as a hoarding strategy in response to competition. This system, and others like Dictyostelium farming (85) and the ectomycorrhizal soil fungus Morchella crassipes farming Pseudomonas putida bacteria as a carbon source (86), can be used to study under what conditions scarce resources are held, so they can be either used later or traded for a greater profit in the future.…”
Section: The Evolution Of Microbial Markets Frommentioning
confidence: 99%
“…Glass fibers were used to simulate hyphae surrounded by liquid films (16,18) and to exclude effects of hyphal activities on bacterial growth and nutrition (38)(39)(40)(41) to avoid additional complexity that might mask effects attributable to the promotion of bacterial dispersal at a lowered ⌿ m .…”
Section: Effects Of Dispersal Network On Bacterial Dispersal At Diffmentioning
confidence: 99%
“…Several studies demonstrated a positive effect of bacteria-fungi interactions on ecosystem services such as increased transformation of anthropogenic and natural compounds in soil (Boonchan et al, 2000;Warmink et al, 2011;Banitz et al, 2011b;Pion et al, 2013a). However, bacterial dispersal along mycelia could also evoke antagonistic effects such as the mutual inhibition or competition between bacteria and fungi (Rousk et al, 2008;Pion et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%